Placental Factors Affecting Birth Weight of Late Onset Severe Preeclampsia - Martadiansyah A; Pangemanan WT; Bernolian N; Maulani H; Theodorus (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Preeclampsia (PE) is one of the leading causes of maternal and perinatal mortality and morbidity. Placental insufficiency is considered as the main pathogenesis in the early onset PE. Objective of the study is to determine the correlation of placenta and birth weight in late onset preeclampsia. A case-control study of prevalence was conducted in Moh. Hoesin Hospital Palembang from August 2015 to August 2016. Samples were women who giving birth in Moh.Hoesin Hospital Palembang. They were divided into two groups, severe preeclampsia as case group and normotensionas control. Data were analyzed by X2, Exact Fisher’s and logistic regression test using SPSS 16.0. There were 180 subjects (90 cases and 90 controls). There was a positive correlation between placental macroscopic and late onset preeclampsia (p=0.009; OR=6.9), in contrast there was only one different placental microvascularisation of 16, between late onset preeclampsia and normotension, the mural or occlusive fibrin thrombi chorion (p=0.005; OR=9.9). Birth weight in late onset preeclampsia tended to be small but still in normal range and it was not statistictly significant (p=0.112; OR=10.4). There was a positive correlation between placental macroscopic and SGA baby on late onset preeclampsia (p=0.026; OR=16.6), but it wasnot proven microscopically. Placenta remains contributed to the pathogenesis of the late onset preeclampsia, but not as dominant as the early one.